SHORT VIDEO APPLICATION USAGE AND FLOW EFFECT ON IMPULSE BUY - Wingdes, Irawan; Luwuk, Yosua Markoliano (Faculty of Economics and Business, Universitas Klabat, 2023)
Mobile Short Video Applications (MSA), offering short video content and often including referral and commercial features, have attracted a substantial user base, appealing to marketers. However, previous research has not specifically focused on how the use of MSA can influence impulsive buying. Therefore, this research aims to fill this gap by integrating the concept of flow (intense engagement with an activity) into the Stimulus-Organism-Response (SOR) Model. In this context, the utilization of MSA serves as the Stimulus, while flow is divided into enjoyment, concentration, and time distortion, acting as the Organism. The observed Response is impulsive buying. A survey-based questionnaire research method was employed, with a sample of 190 university students. Structural equation modeling (SEM) techniques were used to examine the relationships among the constructs, complemented by qualitative analysis. The research findings indicate that the use of MSA significantly influences the experience of flow, which, in turn, affects impulsive purchasing behavior. Flow (enjoyment) exerts the strongest influence on impulsive buying (0.459 correlation), compared to concentration (0.204) and time distortion (0.212). Enjoyment also mediates the relationship between MSA usage and impulsive purchasing. Users tended to engage in spontaneous and unplanned impulsive purchases when they were in a heightened state of flow, predominantly triggered by enjoyment while using MSA, as opposed to concentration or time distortion. The testing model is valid and reliable within a statistical confidence level exceeding 90%, explaining 29.5% of the variance in impulse buying. Keywords: MSA usage, SOR model, flow, impulse buy